Paterimitra pyramidalis from South Australia: scleritome, shell structure and evolution of a lower Cambrian stem group brachiopod. (8th October 2013) - Larsson, Cecilia M.; Skovsted, Christian B.; Brock, Glenn A.; Balthasar, Uwe; Topper, Timothy P.; Holmer, Lars E.; Lane, Phil
Abstract The tommotiid Paterimitra pyramidalis Laurie, 1986, is redescribed based on well‐preserved material from the lower Cambrian Wilkawillina, Wirrapowie and Ajax limestones of the Flinders Ranges, South Australia. The material shows that the scleritome of Paterimitra pyramidalis includes three sclerite morphotypes (S1, S2 and L). Detailed shell microstructure studies show striking similarities with both the paterinid brachiopod Askepasma toddense and the tommotiid Eccentrotheca helenia, which strengthens the suggested evolutionary link between tommotiids and brachiopods. Based on the partly articulated specimens and similarities in shell microstructure and sclerite morphology with Eccentrotheca, Paterimitra pyramidalis is reconstructed as a tube‐dwelling, epifaunal, sessile, filter‐feeder with an organic pedicle‐like attachment structure. The proposed reconstruction of the scleritome comprises a basal unit composed of one S1 and one S2 sclerite, as well as an unresolved number of L sclerites lining a coniform tubular structure.